(untitled) (TAJ: Journal of Teachers Association, 2009)
This study was performed in the Rehabilitation Institute and Hospital for the Disabled (RIHD), Dhaka, Bangladesh from July 1992 to Dec. 1992. Total emergency operations during these six months were 1906. Out of these, 230 cases were open fractures of tibia-fibula, which is 13% of the total. 57% of the victims were in the age group of 15-44 years. 85% were male. Eighty five percent of fractures were caused by road traffic accidents. Methods of treatment were 7 types. 78% fractures were treated by sufficient irrigation debridement and immobilized by long leg cast with making window, most of them falls in type 1 and type 2. In type 3 fractures, after sufficient irrigation and debridement, primary fixation gives the best result for better preservation of function. Average duration of hospital stay is also shown In the paper. doi: 10.3329/taj.v15i2.3915 TAJ December 2002; Vol.15(2): 84-86